Indeks Subjek Volume 33, Tahun 2013 - Indeks Subjek Volume 33, Tahun 2013 (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Acid sulphate land 245Acid-base indicator 320Agroindustry 122, 235, 346AHP 433Algae 371Amino acid 258Ammonium sulphate 377Analysis sistem 227Anthocyanidin 320Anthocyanin content 296Antibacterial 46, 311Antioxidant 155, 311, 371, 384Antioxidant activity 296, 363Antioxidant capacity 324Antocyanin 384Arginine/lysine ratio 2Artificial neural networks 71, 450Ascorbic acid 324